2015
DOI: 10.1007/s40279-015-0379-7
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Ideal Resistance Training Program to Improve Glycemic Control and its Indication for Patients with Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: In terms of glycemic control, RT could be recommended in the early stage of T2DM, especially for patients with relatively poor glycemic control. More benefit would be elicited in less obese patients within a limited range of the BMI. A substantial amount of exercise might be required to stimulate post-exercise glucose uptake, although the dose-dependency was not specifically clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 43 publications
9
74
0
1
Order By: Relevance
“…In parallel with previous finding, Glut 4 level increase with resistance and weight training specially when performed with main muscle groups. Increased insulin sensitivity and glut 4 (a shortcut to glucose transportation system toward muscle tissues) may be helpful in glucose balance and blood glucose monitoring in a diabetic subject; a fact which was found in our study [12][13][14][15][16][17][18]. Regarding fat loss exercises, there are various types of exercise plans in the world [19].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In parallel with previous finding, Glut 4 level increase with resistance and weight training specially when performed with main muscle groups. Increased insulin sensitivity and glut 4 (a shortcut to glucose transportation system toward muscle tissues) may be helpful in glucose balance and blood glucose monitoring in a diabetic subject; a fact which was found in our study [12][13][14][15][16][17][18]. Regarding fat loss exercises, there are various types of exercise plans in the world [19].…”
Section: Discussionmentioning
confidence: 79%
“…It is the procedure of exercise plan which makes significant changes in physiological parameters. This procedure must be monitored by an exercise physiologist to lead to target weight and normal physiological status [14][15][16][17][18]. The results of presented case study report demonstrated the main roles of intricate mechanisms inside the field of sport science regarding diet plan and exercise programme.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…When comparing AT with RT, the benefits of each of these exercise modes on HbA1c is not described adequately [41]. Some studies suggest that AT is more effective than RT in reducing HbA1c levels [89], especially in white Caucasians.…”
Section: The Independent Effects Of At and Rt In Glycemic Control -Efmentioning
confidence: 99%
“…The volume of exercise progressed from 1 set of 8 repetitions up to 3 sets (1x8 to 3x8) and then with increasing resistance according to individual capacity. One review reported that an RT program with 21 or more sets per session had a larger effect size than one with fewer than 21 sets per session [89]. Body resistance, free weights and exercise machines were used in a circuit manner in the exercise sessions to improve variety.…”
Section: Rt-intervention Groupmentioning
confidence: 99%